INTENSITY INDICATORS OF GEODYNAMIC PROCESSES ALONG THE ATLANTIC-ARCTIC RIFT SYSTEM - S. Yu. Sokolov; N. P. Chamov; M. D. Khutorskoy; S. A. Silantiev; С. Ю. Соколов; Н. П. Чамов; М. Д. Хуторской; С. А. Силантьев (Surveys in Geophysics, 2020)
Seismicity, heat flow, seismic tomography data, prerift and synrift magmatism are considered as intensity indicators of geodynamic processes along the Atlantic-Arctic rift system (AARS). In this rift system, several large (over 100 km ) sub-latitudinal displacements of the rift axis are due to left-lateral strike-slip faulting. The AARS segments are distinguished by the age of splitting of continental plates from each other. A dependence is revealed between the current thermal state of the mantle under the AARS and the age of spreading start. This dependence is established from both seismic tomography and heat flow data. In section δ(Vp/Vs), the locations of the main segmenting faults and ‘cold’ anomalies in the upper mantle are coincident. Distributions of total seismic moments are practically synchronous in the depth intervals of 0–13, 13–35, and >35 km. The maximum values above the plumes are represented by higher seismic moments in the surface layer. The main demarcation zones differ in maximum energy release values in the AARS with shearing features. Comparison of these values against the age of the start of spreading processes shows trends of heat flow and medium field tomography in the AARS segments. The trends confirm the thermal interpretation of the seismic tomography data and suggest mantle cooling with age and a decrease in the mean temperatures of the mantle. The main factor causing the sublatitudinal asymmetry of heat flow in the AARS is the impact of Coriolis forces on the magma in the asthenospheric source. Most of the synrift igneous formations seem to be related to the influence of long-lived anomalies in the mantle, which had lower rates of magma generation than those typical of the formation of magmatic provinces. In conditions for spreading and the formation of the oceanic crust, the process followed the principle of energy cost minimization, and the prerift magmatic provinces with the pre-processed crust contributed to the choice and positioning of the AARS trajectory. The plume branches ...